Arginine GlcNAcylation and Activity Regulation of PhoP by a Type III Secretion System Effector in Salmonella - Xue, Juan; Huang, Yuxuan; Zhang, Hua; Hu, Jiaqingzi; Pan, Xing; Peng, Ting; Lv, Jun; Meng, Kun; Li, Shan (Frontiers in Microbiology, 2022)
Salmonella type III secretion system (T3SS) effector SseK3 is a glycosyltransferase delivered directly into the host cells to modify host protein substrates, thus manipulating host cellular signal transduction. Here, we identify and characterize the Arg-GlcNAcylation activity of SseK3 inside bacterial cells. Combining Arg-GlcNAc protein immunoprecipitation and mass spectrometry, we found that 60 bacterial proteins were GlcNAcylated during Salmonella infection, especially the two-component signal transduction system regulatory protein PhoP. Moreover, the Arg-GlcNAcylation of PhoP by SseK3 was detected in vivo and in vitro, and four arginine residues, Arg65, Arg66, Arg118, and Arg215 were identified as the GlcNAcylation sites. Site-directed mutagenesis showed that the PhoP R215A change significantly reduced the DNA-binding ability and arginine to alanine change at all four sites (PhoP 4RA) completely eliminated the DNA-binding ability, suggesting that Arg215 is essential for the DNA-binding activity of PhoP and GlcNAcylation of PhoP affects this activity. Additionally, GlcNAcylation of PhoP negatively regulated the activity of PhoP and decreased the expression of its downstream genes. Overall, our work provides an example of the intra-bacterial activities of the T3SS effectors and increases our understanding of endogenous Arg-GlcNAcylation.